2017
DOI: 10.1007/s10914-017-9404-y
|View full text |Cite
|
Sign up to set email alerts
|

Internal Morphology of Osteoderms of Extinct Armadillos and Its Relationship with Environmental Conditions

Abstract: The most complete and continuous fossil record of armadillos is composed mostly by isolated osteoderms, frequently found in paleontological and archaeological sites that bear continental South American mammals. Their external morphology has been used to define several species. In the last decade, many authors have focused on the internal structure of vertebrate osteoderms using histological and paleohistological studies. These studies allowed identification of useful features in systematic and phylogenetic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…No growth marks were observed in both specimens in longitudinal or transverse sections, with optic microscopic, but thick and rather loose bundles of Sharpey fibers, crossing each other at various acute angles, were seen in transversal sections (Figure. the combining micro-Ct analysis and histological sections, to study the internal anatomy of buckler osteoderms of the extant armadillos Chaetophractus villosus (Desmarest, 1804) and Dasypus hybridus (Desmarest, 1804) (Krmpotic et al 2015, Ciancio et al 2017, provide the data for the association proposed here between the internal cavities and some of the aforementioned internal structures. however, hill (2006) argued that osteoderms of modern armadillos are physically associated with a variety of soft tissues, and in some cases, two or more different tissue types may cause similar osteological features.…”
Section: Internal Microstructure: Histologymentioning
confidence: 99%
See 3 more Smart Citations
“…No growth marks were observed in both specimens in longitudinal or transverse sections, with optic microscopic, but thick and rather loose bundles of Sharpey fibers, crossing each other at various acute angles, were seen in transversal sections (Figure. the combining micro-Ct analysis and histological sections, to study the internal anatomy of buckler osteoderms of the extant armadillos Chaetophractus villosus (Desmarest, 1804) and Dasypus hybridus (Desmarest, 1804) (Krmpotic et al 2015, Ciancio et al 2017, provide the data for the association proposed here between the internal cavities and some of the aforementioned internal structures. however, hill (2006) argued that osteoderms of modern armadillos are physically associated with a variety of soft tissues, and in some cases, two or more different tissue types may cause similar osteological features.…”
Section: Internal Microstructure: Histologymentioning
confidence: 99%
“…Different publications have called these deep circular depressions as hair foramina, neurovascular foramina, or simply foramina. A histological section of the extant D. novemcinctus (the closest extant relative of Riostegotherium yanei, according to Ciancio et al 2017) revealed that the cavity beneath each of these deep and large circular depressions at the external surface also contains a complete hair follicle, radically smaller than its external aperture and embedded entirely within the osteoderm (hill 2006, Krmpotic et al 2012). holmes and Simpson (1931) stated that in all pilose armadillos, hair grows from oblique pits in the hinder margin of the osteoderm, through areas of soft skin in between each one.…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further complicated by accumulating bodies of evidence supporting the idea that defensive morphologies are not exclusively the outcome of predatorprey interactions, but instead have a multifunctional nature shaped by functional tradeoffs (Rivera and Stayton 2011, Magwene and Socha 2013, Broeckhoven et al 2017a. For example, body armour might play an important role during thermoregulation (Endo et al 2009, Krmpotic et al 2015, Broeckhoven et al 2017a, Ciancio et al 2017, Clarac et al 2017). In addition, besides being a product of natural selection, intrasexual aggression might contribute significantly to variation in the expression of defensive traits (Broeckhoven et al 2017b, English 2018.…”
Section: Introductionmentioning
confidence: 99%